2008
DOI: 10.1111/j.1464-410x.2008.07759.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of suspension technique for improving early recovery of urinary continence after radical retropubic prostatectomy

Abstract: The primary outcome measures were the interval to recovery of continence, and the positive margin rates. The continence status was evaluated by a third party using validated questionnaires at baseline before RRP and at 4 and 7 days, and 2 weeks, 1, 3, 6 and 12 months after RRP. RESULTSThe suspension technique resulted in significantly greater continence rates at 1, 3 and 6 months after RRP of 53% vs 20%, 73% vs 47% and 100% vs 83%. KaplanMeier curves also showed that patients in the suspension group had a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Early multi-institutional studies in Japan found the recovery of urinary function following LRP to be slower compared to that following retropubic radical prostatectomy (RRP) (2,3). The operative procedures used to improve the recovery of urinary continence following radical prostatectomy include preserving the fascia covering the levator ani muscle (4), preserving the bladder neck (4), preserving neurovascular bundles (NVBs) (5), securing a longer functional urethra (6,7), reconstructing the posterior musculofascial plate (PMPR) (8)(9)(10), suspending the vesicourethral anastomosis (11) and performing an anterior reconstruction (12).…”
Section: Introductionmentioning
confidence: 99%
“…Early multi-institutional studies in Japan found the recovery of urinary function following LRP to be slower compared to that following retropubic radical prostatectomy (RRP) (2,3). The operative procedures used to improve the recovery of urinary continence following radical prostatectomy include preserving the fascia covering the levator ani muscle (4), preserving the bladder neck (4), preserving neurovascular bundles (NVBs) (5), securing a longer functional urethra (6,7), reconstructing the posterior musculofascial plate (PMPR) (8)(9)(10), suspending the vesicourethral anastomosis (11) and performing an anterior reconstruction (12).…”
Section: Introductionmentioning
confidence: 99%
“…19 trials 7, 1532 evaluated the efficacy of PR, 7 trials 12, 3338 evaluated the efficacy of AS, 4 trials 911, 14 evaluated the efficacy of PR + AR, and 2 trials 39, 40 evaluated the efficacy of PR + AS. Seven of these trials were RCTs 9, 15, 31, 32, 37, 38, 40 . Six trials 11, 18, 25, 29, 32, 33 evaluated IPSS and EPIC urinary domain scores.
Figure 1Selecting the flowchart for the inclusion of studies in the meta-analysis.
…”
Section: Resultsmentioning
confidence: 99%
“…Noguchi et al 26,27 introduced a suspension manoeuvre for the VUA during radical retropubic prostatectomy (RRP). These investigators used anastomotic sutures at the 1:00 and 11:00 o'clock positions to anchor the VUA to the ligated DVC, which results in suspension of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies were prospective studies, but they were not always randomized. 6,28 All studies evaluated continence 3 months postoperatively, 6,[26][27][28] and Noguchi et al 26 performed continence evaluation as early as 1 month after RP. Thus, early postoperative continence evaluation after catheter removal was never assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation